Polymer coated gold nanoshells for combinational photochemotherapy of pancreatic cancer with gemcitabine - Mina Emamzadeh (Nature Portfolio, 2021)
Abstract Pancreatic cancer is one of the most lethal malignancies with limited therapeutic options and dismal prognosis. Gemcitabine is the front-line drug against pancreatic cancer however with limited improvement of therapeutic outcomes. In this study we envisaged the integration of GEM with gold nanoshells which constitute an interesting class of nanomaterials with excellent photothermal conversion properties. Nanoshells were coated with thiol-capped poly(ethylene glycol) methacrylate polymers of different molecular weight via Au–S attachment. It was found that the molecular weight of the polymers affects the in vitro performance of the formulations; more importantly we demonstrate that the EC50 of nanoshell loaded GEM can be suppressed but fully restored and even improved upon laser irradiation. Our proposed nanoformulations outperformed the cytotoxicity of the parent drug and showed confined synergism under the tested in vitro conditions.